Formation of silver nanoparticles induced by poly(2,6-dimethyl-1,4-phenylene oxide) - Kim, HS; Ryu, JH; Jose, B; Lee, BG; Ahn, BS; Kang, YS (AMER CHEMICAL SOC, 2001)
Colloidal silver nanoparticles were easily obtained by reacting AgX (X = BF4, PF6, SbF6, SO3CF3, ClO4, NO3) with poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) in a mixed solvent system of chloroform and methanol in the absence of UV irradiation. Rapid formation of colloidal silver nanoparticles was also observed when a silver salt was added to a chloroform solution containing PPO and 1-hexene. UV-vis spectra and transmission electron micrographs show that the colloidal silver particles formed from these methods are nanosized, stable, and uniformly distributed. PPO was found to be oxidized in the presence of a silver salt to give quinone and quinone derivatives which were analyzed by GC-Mass. A plausible mechanism for the formation of silver nanoparticles is proposed on the basis of the redox reaction of PPO in the presence of a silver salt.
Keywords: COLLOIDAL SILVER; PHOTOCHEMICAL FORMATION; CLUSTERS; SURFACE; GOLD; REDUCTION; OXIDATION; POLYMER; SALTS; SOLS